A new algorithm-based type-2 fuzzy controller for diabetic patient. (26th June 2007) - Singh, Madhusudan; Srivastava, Smriti; Gupta, J.R.P.; Hanmandlu, M.
In this paper, a new control algorithm is developed, which uses type-2 fuzzy sets for automatic insulin delivery rate. Type-2 fuzzy sets have been used to handle uncertainties in the rules due to the inability of type-1 fuzzy sets in such cases. As the stability of the model is also highly dependent on the learning of the system, we have used Lyapunov Stability (LS) in combination with Fuzzy Differential (FD) for learning. A measure of the performance of different controllers is taken by incorporating parametric uncertainty into the model. The effectiveness of the proposed controller is demonstrated on type I diabetes patient.